PEMANFAATAN LIMBAH BIOMASSA TEMPURUNG KELAPA UNTUK ALAT TEKNOLOGI PENGERING PAKAIAN BERBASIS ARDUINO UNO - Mutia Febri Irdayanti; Krisman Krisman; Juandi Muhammad; Annisa Alqorina (Universitas Riau, 2023)
Research on the utilization of coconut shell biomass waste for clothes dryer technology based on Arduino Uno has been carried out using the experimental method. This Arduino Uno-based dryer technology uses biomass energy from coconut shells with a mass of 2,000 grams for thin clothes and 4,000 grams for thick clothes. Observations were made based on the amount of coconut shell mass and the type of clothing used at 10 minute intervals. The results for a mass of 2,000 grams of coconut shell reached the highest temperature value with an average source temperature of 61.32°C, an average temperature in the drying chamber of 54.53°C with a minimum humidity of 19.5%, while the results for a mass of 4,000 grams coconut shell reached the highest temperature value with an average source temperature of 100.46°C, an average temperature in the drying chamber of 94.62°C with a minimum humidity of 21.1%.